2012, No. 11, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Financial accounting and practice Jonas Žaptorius, Sustainability accounting: a brief history and concept, 7 Kristina Rudžionienė, Erika Krakauskaitė, Fair value measurement in accounting, 18 Akvilė Stulpinaitė, Judita Biveinytė, The comparative analysis of the 12th Business Accounting Standard and International Accounting Standards regulating accounting of tangible long-term assets, 28 Jonas Mackevičius, Jokūbas Leipus, Peculiarities of Muslim banks’ accounting, 40 Martynas Novikovas, Transfer pricing control and audit in Lithuania, 51 Management accounting and practice Lina Veličkienė, Kristina Rudžionienė, Rūta Klimaitienė, Job – costing method in small service companies, 66 Lionius Gaižauskas, Budgets preparing and application problems in the Lithuanian enterprises, 76 Svetlana Vegera, Accounting of environmental and social land rent in modern system of economic relations: problems and principles of methodology, 91 Financial analysis and evaluation Ramunė Budrionytė, Laimutė Kazlauskienė, Rasa Subačienė, System of ratio analysis of tourism companies, 98 Gerda Venckevičiūtė, Gražina Jatuliavičienė, Performance measurement systems development: from financial to corporate perspective, 116 Stasys Valentinavičius, The theoretical aspects of evaluation company’s investment preference, 127